Vibroacoustic Measurements and Simulations Applied to External Gear Pumps. An Integrated Simplified Approach - CARLETTI, Eleonora; MICCOLI, Giuseppe; PEDRIELLI, Francesca; PARISE, Giorgio (Archives of Acoustics, 2016)
This paper describes the development phases of a numerical-experimental integrated approach aimed at obtaining sufficiently accurate predictions of the noise field emitted by an external gear pump by means of some vibration measurements on its external casing. Harmonic response methods and vibroacoustic analyses were considered as the main tools of this methodology. FFT acceleration spectra were experimentally acquired only in some positions of a 8.5 cc/rev external gear pump casing for some working conditions and considered as external excitation boundary conditions for a FE quite simplified vibroacoustic model. The emitted noise field was computed considering the pump as a ‘black box’, without taking into account the complex dynamics of the gear tooth meshing process and the consequent fluid pressure and load distribution. Sound power tests, based on sound intensity measurements, as well as sound pressure measurements in some positions around the pump casing were performed for validation purposes. The comparisons between numerical and experimental results confirmed the potentiality of this approach in offering a good compromise between noise prediction accuracy and reduction of experimental and modelling requirements.